PRODUCTION PLANNING AND RAW MATERIALS SUPPLY TO MEET FLUCTUATIVE DEMAND FOR LIVESTOCK FEED FLOUR - arief, Zainal (Archives of Business Research, 2018)
Production is creating goods and services, CV Bulu Nusantara is a company that processes poultry feathers, fish bones, beef bones, shells into dough flour for livestock feed. Sometimes these companies encounter overproduction and sometimes production shortages. The researcher intends to run production planning and raw material need planning that can meet fluctuative demand and minimize production costs with JIP and MRP approaches. From the research carried out, obtained forecasting demand result for period June 2017 - May 2018 for feather flour, fish flour, bone meal and crab flour for 191,040 kg, 144,876 kg, 135,189 kg and 158,028 kg. From production master schedule made based on forecasting and production capacity result, a plan is obtained for June 2017 - May 2018 of Rp. 1,858,057,638. Material requirements planning (MRP) can be seen when, how many orders, how many times the order for raw materials is within 1 year, so that the raw material inventory is optimal in accordance with the master production schedule, in addition to MRP also obtained for the total cost of raw materials for planning period June 2017 - May 2018 amounting to Rp. 16,710,197,190. From the cost of labor and raw materials, total production planning is Rp. 18,568,254,838, if the total cost of production planning is compared to the total production costs of the company in 2016-1017 amounting to Rp. 18,690,250,000 then the difference in annual production costs of Rp. 121,995,170. This means that by implementing JIP and MRP systems the company will save production costs by Rp. 121,995,170.